Optimization of In-house PCR Assay for Human BCL-2 Gene - Saraswati, Henny; Nauli Pulungan , Anita; Naroeni, Aroem; Fauzi, Esa (International Journal of Psychosocial Rehabilitation, 2020)
BCL-2 gene is present on human chromosome 18 and contributes in regulating the mechanism of apoptotic cells. Mutations and overexpression of the BCL-2 gene are known to be associated with several cancers. Comprehensive research on the role of BCL-2 in the incidence of cancer is needed to understand course of the diseases and treatment. Polymerase Chain Reaction (PCR) method for copying the BCL-2 gene can be used in this research. Optimization of the in-house PCR reaction was carried out to determine the optimal conditions of the PCR reaction on the doubling of the BCL-2 gene. In-silico analysis of the primer design produces three pairs of primers used in the optimization process. The parameters used in this optimization are the annealing temperature and primer concentration used. Validation of the results of optimization of the PCR reaction was carried out by biopsy samples of tumor tissue of patients with cervical tissue abnormalities. The result showed that the best primer pairs of the reaction is primer C with optimal annealing temperature is 570C and 800 nM concentration.